Enuresis Persisting into Adulthood - Shadpour, Pejman; Shiehmorteza, Masoud (Urology Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Introduction: Nocturnal enuresis is a very common finding in children to the extent that many families and caregivers, alike, may dismiss it as a developmental stage rather than a disease. Persistence of nocturnal enuresis into adulthood, however, has received little discussion and is surrounded by fallacies. Materials and Methods: All existing literature cited in PubMed between 1970 and 2005 were reviewed using the search entries â€œnocturnal enuresis AND adultâ€. Result: Of the 220 papers reviewed, enuresis persisting into adulthood was covered in only 87. Those aspects pertinent to this subset of patients were placed in focus. Conclusion: In contrast to the numerous researches on childhood enuresis, persistent adulthood enuresis is an underdiscussed subject, distinct in a few aspects of its etiology and management described herein.